2021
DOI: 10.2355/isijinternational.isijint-2019-477
|View full text |Cite
|
Sign up to set email alerts
|

Steam Reforming of Methane on Sponge Iron: Influence of Gas Composition on Reaction Rate

Abstract: Direct Reduction processes use gases (CO and H 2 ) for iron reduction and production of sponge iron or direct reduced iron (DRI). The generation of this gas occurs through methane reforming, which can be done in a reformer or inside the reduction shaft with the sponge iron as a catalyst. The latter occurs in the auto-reforming processes. The kinetics of steam reforming of methane catalyzed by sponge iron was studied at temperatures between 875°C and 1 050°C. Results showed that sponge iron acts as a catalyst a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…H O(g) O(ads) H g In a paper published previously, 11) the present authors showed results of the catalytic activity of sponge iron in steam reforming of methane. Gas composition with a higher H 2 /H 2 O ratio resulted in higher conversions of methane, which agrees with the mechanism proposed by Münster and Grabke.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…H O(g) O(ads) H g In a paper published previously, 11) the present authors showed results of the catalytic activity of sponge iron in steam reforming of methane. Gas composition with a higher H 2 /H 2 O ratio resulted in higher conversions of methane, which agrees with the mechanism proposed by Münster and Grabke.…”
Section: Introductionmentioning
confidence: 51%
“…The chemical composition of such pellets is shown in Table 1. The pellet size distribution of Pellet Vale can be found in the previous paper 11) with an average diameter of 12.6 mm. Pellet A was supplied in two size ranges that were combined in the same proportion, 8 mm to 12 mm and 12 mm to 16 mm, resulting in an average diameter of 12 mm.…”
Section: Experimental Methodsmentioning
confidence: 95%
See 3 more Smart Citations